(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Background: The stature prediction occupies a relatively central position both in anthropological research and forensic practice especially in cases where bodies are found in mutilated condition or only skeletal remains are sent for examination. It is well known fact that there is definite correlation of height with different measurements of bones. Stature varies with race, sex, climatic condition. Moreover, each race requires its own formula for height estimation because of variations exist in population of different geographical region. In India, where racial and ethnic variations are well known, region wise study of this kind is necessary. Aim: Present study was done to estimate stature from skull length and breadth in Madhya Pradesh population. Method: Study was conducted amongst 150 males and 150 females who are of age group 18–25 years. All the participants are born and brought up in Madhya Pradesh only. Height, head length (HL) and head breadth (HB) was taken by standard anthropometric instruments and technique. Results: Linear regression equation for both sexes is calculated. Conclusion: Stature estimation can be done from HL and HB by these formulae which are specific for Madhya Pradesh population.